The art and science of drug titration - Aisling R. Caffrey; Eric P. Borrelli (SAGE Publishing, 2020)
A "one-size-fits-all" approach has been the standard for drug dosing, in particular for agents with a wide therapeutic index. The scientific principles of drug titration, most commonly used for medications with a narrow therapeutic index, are to give the patient adequate and effective treatment, at the lowest dose possible, with the aim of minimizing unnecessary medication use and side effects. The art of drug titration involves the interplay of scientific drug titration principles with the clinical expertise of the healthcare provider, and an individualized, patient-centered partnership between the provider and the patient to review the delicate balance of perceived benefits and risks from both perspectives. Drug titration may occur as up-, down-, or cross-titration depending on whether the goal is to reach or maintain a therapeutic outcome, decrease the risk of adverse effects, or prevent withdrawal/discontinuation syndromes or recurrence of disease. Drug titration introduces additional complexities surrounding the conduct of clinical trials and real-world studies, confounding our understanding of the true effect of medications. In clinical practice, wide variations in titration schedules may exist due to a lack of evidence and consensus on titration approaches that achieve an optimal benefit-harm profile. Further, drug titration may be challenging for patients to follow, resulting in suboptimal adherence and may require increased healthcare-related visits and coordination of care amongst providers. Despite the challenges associated with drug titration, it is a personalized approach to drug dosing that blends science with art, and with supportive real-world outcomes-based evidence, can be effective for optimizing pharmacotherapeutic outcomes and improving drug safety.